THE ROLE OF A GRATIFICATION REPORTING SYSTEM AS AN INTERNAL CONTROL INSTRUMENT IN FRAUD-PREVENTION: A STUDY AT LAZNAS DT PEDULI - Dini Meilani; Iwan Setiawan; Lina Yulianti (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the role of the gratification reporting system as an internal control instrument in fraud-prevention efforts at LAZNAS DT Peduli.Methods: This study uses a qualitative case study approach. Data were collected through in-depth interviews with internal parties at LAZNAS DT Peduli, observation of the implementation of the Gratification Reporting System, and analysis of policy documents and internal control procedures. Data analysis was conducted using Miles and Huberman's interactive model, which includes reduction, presentation, and conclusion drawing, while data validity was tested through triangulation.Results: The study found that the Gratification Reporting System implemented through the SIMPUL LAZ DT Peduli platform effectively functions as an internal control instrument by integrating COSO-based elements and fostering transparency through mandatory reporting, supervision, and ethical reinforcement within zakat management.Conclusion and suggestion: The system significantly contributes to fraud prevention by reducing the opportunity and rationalization factors identified in the Fraud Diamond framework. Opportunity is constrained through mandatory reporting procedures, layered supervision, and verification by the Gratification Control Unit, which limit individuals’ ability to misuse authority. Rationalization is weakened through continuous ethical reinforcement, religious values, and an organizational culture that promotes integrity and accountability in managing public trust. The system is recommended as a model for zakat and public institutions, provided that ongoing ethical training and cultural reinforcement are maintained to sustain its effectiveness. Keywords: Fraud Prevention, Gratification Reporting System, Internal Control, LAZNAS.